Succession‐induced trait shifts across a wide range of NW European ecosystems are driven by light and modulated by initial abiotic conditions - Douma, Jacob C; de Haan, Martin W. A; Aerts, Rien; Witte, Jan‐Philip M; van Bodegom, Peter M (The Journal of ecology, 2012)
1. For truly predictive community ecology, it is essential to understand the interplay between species traits, their environment and their impacts on the composition of plant communities. These interactions are increasingly understood for various environmental drivers, but our understanding of how traits, in general, change during succession is still modest. We hypothesize that (initial) abiotic conditions other than light drive the successional dynamics of other traits. The idea that different initial abiotic conditions lead to different trait trajectories during succession was predicted long ago but has never been tested for traits. 2. In this study, we compared the successional (decades to centuries) trait trajectories of 19 ecosystem types in low‐altitude NW Europe using a database including >4700 plots. We tested which traits (out of a total of 12, including those associated with light competition strategies) show consistent shifts across ecosystems. Additionally, we investigated, through a novel partitioning of trait differences (using partial principal component analyses), whether abiotic factors can explain trait shifts that occur over and above light‐induced trait shifts. 3. We show that canopy height, woodiness, leaf size and seed mass increase, and flowering onset and flowering duration decrease consistently with succession across ecosystems, while leaf economic traits and life span showed a mixed response during succession. Accounting for the effect of height revealed that the initial and prevailing abiotic conditions – particularly soil moisture – co‐determine trait shifts during succession. Therefore, different initial starting conditions may lead to different trajectories in trait space, most notably due to the differential response of specific leaf area (SLA), leaf nitrogen content and life span. For example, SLA decreases in seres that become drier over time (initially very wet), while it increases in seres that become wetter over time (initially very dry). 4. Synthesis. Our novel approach of partitioning successional trait shifts between the influence of competition for light and other abiotic factors showed that trajectories of ecosystems through trait space can be explained by a combination of the two: a universal response to changing light availability and a specific response depending on initial abiotic conditions.